2014
DOI: 10.1111/1744-7917.12047
|View full text |Cite
|
Sign up to set email alerts
|

Intraguild predation among Scolothrips longicornis (Thysanoptera: Thripidae), Neoseiulus californicus and Typhlodromus bagdasarjani (Acari: Phytoseiidae) under laboratory conditions

Abstract: This study was carried out on the ability of predatory thrips Scolothrips longicornis Priesner to feed on 2 phytoseiid species and vice versa. Also the effect of predation of Neoseiulus californicus (McGregor) on Typhlodromus bagdasarjani Wainstein and Arutunjan and vice versa was evaluated. The larvae, prepupae, and pupae of thrips and the eggs, larvae, and protonymphs of phytoseiids were selected as intraguild prey. The intraguild predation (IGP) among S. longicornis and 2 phytoseiid species was unidirection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 43 publications
1
10
1
Order By: Relevance
“…S. longicornis revealed predation rate on heterospecific young or old nymph of O. albidipennis. However, in contrast to the earlier study, which showed that S. longicornis is monophagus and was not able to feed on larval stages of two phytoseiid predators, Neoseiulus californicus and Typhlodromus bagdasarjani (Farazmand et al, 2013).…”
Section: Discussioncontrasting
confidence: 98%
“…S. longicornis revealed predation rate on heterospecific young or old nymph of O. albidipennis. However, in contrast to the earlier study, which showed that S. longicornis is monophagus and was not able to feed on larval stages of two phytoseiid predators, Neoseiulus californicus and Typhlodromus bagdasarjani (Farazmand et al, 2013).…”
Section: Discussioncontrasting
confidence: 98%
“…According to our results, P. persimilis and T. bagdasarjani could lay eggs when provided with heterospesifics, both in presence and absence of shared prey. Some studies showed that P. persimilis was unable to produce eggs on some stages of intraguild prey (Walzer and Schausberger 1999a;Ghasemloo et al 2016) but in agreement with our results, Farazmand et al (2015b) and Ghasemloo et al (2016) reported oviposition by T. bagdasarjani on intraguild prey stages. Research has reported that a generalist predator was able to sustain oviposition on heterospecifics (Schausberger 1997;Walzer and Schausberger 1999a;Hatherly et al 2005;Meszaros et al 2007;Momen and Abdel-Khalek 2009;Negloh et al 2012).…”
Section: Prey Predator Speciessupporting
confidence: 93%
“…2016) but in agreement with our results, Farazmand et al . (2015b) and Ghasemloo et al . (2016) reported oviposition by T. bagdasarjani on intraguild prey stages.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations